Characterization and Evaluation of Tobacco Stem Waste Liquid Smoke as an Eco-Friendly Tofu Bio-preservation - Purwantisari, Susiana; Rasyid, Rido Baharudin Ar; Wardana, Tegar Pratama Kayong; Arfieta, Frisca; Wibisono, Shafa’ Khairunnisa; Jaya, Myra Ivana Yulia; Dafip, Muchamad (Universitas Negeri Semarang, 2025)
Tofu preservation often uses unsafe chemicals, especially formaldehyde, that trigger health problems in humans. Therefore, it is necessary to develop preservation methods that are both effective and safe for human health. Liquid smoke derived from tobacco stem waste is well known to contain antioxidant and antimicrobial properties that may be suitable for use as a preservative compound for tofu. This study aims to evaluated the potential of tobacco stem liquid smoke as a natural preservative by analyzing its chemical profile, antimicrobial efficacy, and impact on tofu characteristics. Tofu samples were soaked in 0%, 5%, and 15% liquid smoke solutions and stored at room temperature for 24 hours. GC-MS analysis confirmed the presence of key compounds: phenolics (51.21%), fatty acids (30.82%), and ketones (17.96%). The treatment significantly improved preservation metrics, reducing the microbial load by up to 81% and lowering the pH to 5.1. The moisture content was reduced while protein levels were proportionally maintained. The 15% concentration provided the highest antimicrobial effect, enhanced aroma, and imparted a distinctive smoky flavor, yet the treatment was preferred by panelists for its better preservation of original color and soft texture. These findings highlight the potential of tobacco stem liquid smoke as a natural, low-cost preservative for tofu, promoting the valorization of biomass waste into value-added products.